Self-monitoring with home based fecal calprotectin is associated with increased medical treatment. A randomized controlled trial on patients with inflammatory bowel disease - Östlund, Isak; Werner, Mårten; Karling, Pontus (Scandinavian journal of gastroenterology, 2021)
Self-monitoring of inflammatory bowel disease (IBD) with the assistant of telemedicine and home-based fecal calprotectin (FC) tests is evolving in the management of IBD. We performed a randomized controlled trial to investigate the compliance and effects of the model IBD-Home in patients with IBD. Patients were randomized to IBD-Home + standard care (n = 84) or standard care alone (n = 74). Intervention with IBD-Home included IBDoc ® FC test kits and a digital application used for answering symptom questionnaires (Abbvie/Telia). They were instructed to use these on demand during a 12-month period. Data was collected retrospectively from medical records. Patients who completed the intervention were phoned and asked to answer a survey about the experience of IBD-Home. The compliance to IBD-Home was low (29%). Women were more compliant compared with men (43% vs 17%, p < .001). A significantly higher proportion of patients in the IBD-Home group increased their medical treatment during the study period in comparison to control subjects (33% vs 15% p = .007) and there was an association between an increase in treatment and compliance to IBD home (multivariate odds ratio 3.22; 95 th confidence interval 1.04 − 9.95). Overall patients reported a positive experience with slight technical difficulties. Self-monitoring with home based fecal calprotectin and a digital application was found feasible and appreciated by compliers. Compliance to the IBD-Home model was more common in women and associated with an increased treatment for IBD.